Graphene‐Modified Mesoporous Iron Phosphate as Superior Binary Sulfur Host for Lithium–Sulfur Batteries. Issue 5 (21st February 2020) - Jin, Fan; Wang, Bo; Ning, Yu; Zhang, Zekun; Yang, Jing; Zhang, Han; Wang, Dianlong; Zhou, Yu
Abstract : Lithium–sulfur batteries (LSB) are considered to have great research value and application prospects in the future due to their high theoretical energy density, inexpensive characteristics, and environmental friendliness. However, the poor electronic conductivity, large volume change, and shuttle effect of the sulfur cathode seriously hinder the commercial application of LSBs. Herein, a graphene‐modified mesoporous amorphous FePO4 (G/FP) binary host is synthesized using a mild one‐step hydrothermal method. The FePO4 (FP) component with strong polarity plays a crucial role in chemical adsorption and conversion of polysulfides, thus inhibiting the shuttle effect during the cycle process. The graphene (G) framework ensures the electronic conductivity and physically adsorbs polysulfides to improve the utilization of active sulfur. The reasonable porous structure of the G/FP matrix guarantees fast Li + transport and more electrochemical reactive sites, thereby enabling the excellent electrochemical performance of the G/FP/S cathode. The prepared G/FP/S cathode with a high initial discharge specific capacity of 1469.5 mAh g −1 delivers a stable capacity of 840.7 mAh g −1 at 0.2 C after 300 cycles and 656.7 mAh g −1 at 1.0 C after 800 cycles as well as an excellent rate performance (651.8 mAh g −1 at 5.0 C) at a relatively large sulfur loading of 3.1 mg cm −2 . Abstract : A graphene‐modified mesoporous FePO4 binary sulfur host with a unique heterostructure is constructed, in which mesoporous FePO4 nanoparticles play a key role for the chemical adsorption of soluble lithium polysulfide and accelerating the conversion process between long‐chain lithium polysulfide and short‐chain Li2 S2 /Li2 S, thus effectively inhibiting the "shuttle effect" during the charge and discharge process.